Predictors Factors of Mortality Hepatocelullar Carcinoma Patients RSD dr. Soebandi Jember 2018-2020 - Roan Pratama Putra; Irawan Fajar Kusuma; Adelia Handoko (Journal of Agromedicine and Medical Sciences, 2022)
Liver cancer, predominantly Hepatocellular Carcinoma (HCC), is a tumor that originates from hepatocytes and is clinically progressive. In Indonesia, according to the Ministry of Health in 2019, liver cancer is the second most common cancer in men, amounting to 12.4 per 100,000 population with an average death rate of 7.6 per 100,000 population. There are very few studies on HCC in RSD dr. Soebandi Jember. This study aims to determine the characteristics and factors that can be predictors of death in HCC patients. This study uses an observational analytic research type with a case-control research design. The data of this study used secondary data from the medical records of HCC patients at RSD dr. Soebandi Jember, as well as primary data in the form of telephone interviews. The results of this study with a total of 72 samples showed that there was a significant difference between liver cirrhosis and HCC patient mortality within 90 days (p = 0.005), and could be used as a predictor of HCC mortality (OR = 17.15; 95% CI = 1.532-192.017). Keywords: HCC, predictors of death, HCC mortality